The Warner Brothers - Yogerst, Chris, 1983- (Book collections on Project MUSE., 2023)
"One of the oldest and most recognizable studios in Hollywood, Warner Bros. is considered a juggernaut of the entertainment industry. Since its formation in the early twentieth century, the studio has been a constant presence in cinema history, responsible for the creation of acclaimed films, blockbuster brands, and iconic superstars. These days, the studio is best known as a media conglomerate with a broad range of intellectual property, spanning movies, TV shows, and streaming content. Despite popular interest in the origins of this empire, the core of the Warner Bros. saga cannot be found in its commercial successes. It is the story of four brothers-Harry, Albert, Sam, and Jack-whose vision for Hollywood helped shape the world of entertainment as we know it. In The Warner Brothers, Chris Yogerst follows the siblings from their family's humble origins in Poland, through their young adulthood in the American Midwest, to the height of fame and fortune in Hollywood. With unwavering resolve, the brothers soldiered on against the backdrop of an America reeling from the aftereffects of domestic and global conflict. The Great Depression would not sink the brothers, who churned out competitive films that engaged audiences and kept their operations afloat-and even expanding. During World War II, they used their platform to push beyond the limits of the Production Code and create important films about real-world issues, openly criticizing radicalism and the evils of the Nazi regime. At every major cultural turning point in their lifetime, the Warners held a front-row seat. Paying close attention to the brothers' identities as cultural and economic outsiders, Yogerst chronicles how the Warners built a global filmmaking powerhouse. Equal parts family history and cinematic journey, The Warner Brothers is an empowering story of the American dream and the legacy four brothers left behind for generations of filmmakers and film lovers to come"--